2012
DOI: 10.1093/annonc/mdr439
|View full text |Cite
|
Sign up to set email alerts
|

Minimising critical organ irradiation in limited stage Hodgkin lymphoma: a dosimetric study of the benefit of involved node radiotherapy

Abstract: Reduction from IFRT to INRT decreased the volumes of lungs, breasts and thyroid receiving high-dose radiation, suggesting the potential to reduce long-term second malignancy risks. VMAT may be useful for patients with pre-existing heart disease by minimising further cardiac toxicity risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…With regard to cardiac doses, dose or volume dependence for late toxicity remains unclear [29]. Other studies [18,24] have also included the proximal coronary arteries as a possible region that may relate to late complications; we were not able to reliably contour this region with our scan data/phase of contrast/experience. Campbell et al [18] found that although INRT offered a reduction in whole heart doses, the dose to proximal coronary arteries was not reduced.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…With regard to cardiac doses, dose or volume dependence for late toxicity remains unclear [29]. Other studies [18,24] have also included the proximal coronary arteries as a possible region that may relate to late complications; we were not able to reliably contour this region with our scan data/phase of contrast/experience. Campbell et al [18] found that although INRT offered a reduction in whole heart doses, the dose to proximal coronary arteries was not reduced.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies [18,24] have also included the proximal coronary arteries as a possible region that may relate to late complications; we were not able to reliably contour this region with our scan data/phase of contrast/experience. Campbell et al [18] found that although INRT offered a reduction in whole heart doses, the dose to proximal coronary arteries was not reduced. Data from Paumier et al [24] suggests that additional techniques, such as deep inspiratory breath hold, are required to reduce the dose to the proximal coronary arteries.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Modern therapies, such as involved field radiotherapy, may reduce the long-term secondary malignancy risk from radiation treatments and protect the heart and coronary arteries by reducing mean radiation dose to the heart. 29 By limiting normal tissue exposure, these methods may be more important than total dose in terms of risk of long-term toxicities. 30 As late-effects mortality data on survivors treated more recently will not be available for many years, our model provides important insight by leveraging the best available clinical data now, and suggests that if involved field radiation reduces CRT excess cardiac risk by 50% or eliminates CRT excess second cancer risk all together, CT would still be associated with more favorable OS.…”
mentioning
confidence: 99%
“…21 Dosimetric studies demonstrate that reducing the radiotherapy field from IFRT to INRT significantly reduces the radiation dose to lungs, breast, and thyroid. 29,30 Using dosimetric parameters as surrogate endpoints for toxicity, it is reasonable to extrapolate that these dose reductions are likely to translate into lower risks of radiation-induced toxicities and second malignancies in long-term survivors. Our group has retrospectively evaluated the impact of reduced radiotherapy field sizes on patterns of relapse and survival in limited-stage Hodgkin lymphoma and follicular lymphoma.…”
Section: -3mentioning
confidence: 99%